Composite membrane for directionally modifying MXene by using alpha-cyclodextrin and preparation method of composite membrane
By directionally modifying α-cyclodextrin between MXene nanosheets, a highly selective and high-flux ion separation membrane is formed, solving the balance problem between selectivity and flux in existing ion separation membranes and achieving efficient ion selectivity and rapid transport.
Patent Information
- Application Number
- CN202511811455.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-04
- Publication Date
- 2026-01-02
- Estimated Expiration
- 2045-12-04
AI Technical Summary
Existing ion separation membranes struggle to achieve a balance between high ion selectivity and high ion flux. In particular, the disordered channel structure of polymer membranes leads to low ion selectivity, while the functional molecule modification methods of inorganic two-dimensional material membranes are prone to clogging the channels.
A composite membrane with MXene was modified by α-cyclodextrin. By forming directional interlayer channel entrances between MXene nanosheets, and connecting α-cyclodextrin to the ends of MXene nanosheets, sub-nano channels were formed, ensuring rapid transport of monovalent ions and achieving selective separation.
The α-cyclodextrin-modified MXene composite membrane achieves simultaneous improvement in selectivity and throughput, exhibiting excellent performance in the selectivity of monovalent and divalent ions, and also has good structural stability, extending its service life.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of ion separation membrane materials, and particularly relates to a composite membrane of MXene modified by α-cyclodextrin and a preparation method thereof. BACKGROUND
[0002] Ion separation membranes have a wide application prospect in the fields of energy, resource extraction, environmental governance, etc. due to their low energy consumption, environmental friendliness, and no phase transition. For example, the extraction of lithium ions from salt lakes or waste batteries, the separation of rare metal ions from seawater, and the selective proton conduction in fuel cells all rely on efficient ion selective separation membranes. At present, the separation membranes that are more maturely applied include three categories of polymer membranes, inorganic membranes, and composite membranes. Among them, polymer membranes are widely used due to their convenient processing and good mechanical properties, but their channel structure is usually disordered, and it is difficult to precisely control at the molecular scale, so the ion selective separation performance is often low. For example, the Li + / Mg 2+ selectivity (i.e. the ratio of Li + flux to Mg 2+ flux) is only 2.8. Inorganic two-dimensional material membranes, such as transition metal carbide / nitride (MXene) membranes, have become a research hotspot for membrane separation in recent years due to their controllable interlayer nanochannel structure and rich surface chemical tunability. Among them, MXene materials are widely studied due to their strong rigidity, rich surface end groups (-O, -OH, -F), and excellent electrical conductivity.
[0003] MXene membranes form sub-nanometer channels for ion sieving through the layer-by-layer stacking of nanosheets, but a large number of studies have shown that only size effect cannot achieve high ion selectivity. Therefore, researchers try to introduce functional molecules that can interact with hydrated ions into the interlayer channels of MXene nanosheets by utilizing the rich surface end groups of MXene nanosheets, and the difference between the interaction between the hydrated ions and the functional groups in the sub-nanometer confined channels is enhanced to improve the ion selectivity. Although this strategy of modifying MXene nanosheets with functional molecules can significantly improve the ion selectivity, the random and large distribution of functional molecules in the two-dimensional interlayer channels can block the ion transport channels, thereby causing a loss in ion transport rate. The "permeability-selectivity" balance has become the main bottleneck for the development of ion separation membranes.
[0004] Therefore, there is an urgent need to provide a membrane material in which the modification molecules can be distributed in the sub-nanometer channels in a directed manner and a preparation method thereof, so as to improve the ion selectivity and transport rate. SUMMARY
[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide a composite membrane of α-cyclodextrin-directed modified MXene, its preparation method and application, so as to improve ion selectivity and ion flux.
[0006] Technical solution: The composite membrane of MXene directionally modified with α-cyclodextrin described in this invention comprises:
[0007] MXene nanosheets, which are stacked layer by layer to form sub-nanometer channels that facilitate the passage of ions;
[0008] α-Cyclodextrin, which is attached to the ends of MXene nanosheets to form interlayer channel entrances for sub-nanochannels.
[0009] Furthermore, the MXene nanosheets are Ti3C2T x Ti2CT x V2CT x or Nb2CT x One of them.
[0010] Furthermore, the mass of the MXene nanosheets is 3-15% of the mass of α-cyclodextrin.
[0011] The present invention also provides a method for preparing the above-mentioned α-cyclodextrin-directed modified MXene composite membrane, comprising the following steps:
[0012] (1) An aqueous dispersion of non-oxidized MXene nanosheets was prepared by a reduction-enhanced chemical exfoliation method;
[0013] (2) Dissolve α-cyclodextrin and nicotinic acid salt in water to form a mixed aqueous solution, and stir to form a cyclodextrin inclusion complex solution;
[0014] (3) Add the aqueous dispersion of MXene nanosheets to the aqueous solution of cyclodextrin inclusion complex and stir to obtain the film-forming solution;
[0015] (4) The membrane-forming solution is deposited onto the base membrane by batch filtration. Each batch is washed to remove nicotinic acid molecules after deposition. After filtration, the membrane is dried to obtain the composite membrane.
[0016] Furthermore, the reduction-enhanced chemical exfoliation method for preparing an aqueous dispersion of MXene nanosheets includes the following steps: adding lithium fluoride and MAX powder uniformly to a concentrated hydrochloric acid solution and stirring until homogeneous; then etching at 25-45°C for 24 h and centrifuging to obtain multilayer MXene nanosheets; then adding a reducing agent to the MXene nanosheet aqueous solution, performing ultrasonic exfoliation under an inert atmosphere, and then centrifuging and washing to obtain a single-layer non-oxidized MXene nanosheet dispersion.
[0017] Furthermore, the mass ratio of the reducing agent to MAX powder is (0.5-2):1, and the reducing agent is preferably vitamin C.
[0018] Furthermore, the nicotinate is one of sodium nicotinate, potassium nicotinate, or lithium nicotinate.
[0019] Furthermore, the mass ratio of nicotinic acid salt to α-cyclodextrin is (5-10):1; the pH of the mixed aqueous solution is 6-9; and the stirring time is 24-48 h.
[0020] Furthermore, the concentration of MXene nanosheets in the film-forming solution is 0.05-0.2 g / L, and the stirring reaction time is 2-6 h.
[0021] Furthermore, the base film is any one of PES, PVDF, or Nylon, and the pore size of the base film is 0.1-0.22 μm.
[0022] Beneficial effects: Compared with the prior art, the significant effects of the present invention are as follows:
[0023] (1) The α-cyclodextrin-modified MXene composite membrane provided by the present invention has interlayer channel entrances formed by α-cyclodextrin that can select for monovalent ions, with a monovalent / divalent ion selectivity exceeding 10. 3 Furthermore, the sub-nanometer channels formed by MXene are untouched by modified molecules, allowing for unimpeded transport of monovalent ions and ensuring rapid transport of these ions, achieving a monovalent ion flux of 0.1 mol m. -2 h -1 It can be seen that the composite membrane described in this invention can achieve simultaneous improvement in ion selectivity and ion flux. Moreover, after seven days of ion separation testing, the morphology and structure of the composite membrane did not change significantly, indicating that the structural stability of the composite membrane is improved and its service life is extended.
[0024] (2) The composite membrane preparation method provided by the present invention increases the negative charge density at the narrow side port of α-cyclodextrin, inducing it to be oriented to bind with the edge of positively charged MXene nanosheets; the modification method is simple and easy to extend, and the effect is significant. Attached Figure Description
[0025] Figure 1 This is a schematic diagram of the composite membrane of the present invention;
[0026] Figure 2 This is a schematic diagram illustrating the mechanism of transport of monovalent and divalent ions in the composite membrane α-CD@MXene of this invention;
[0027] Figure 3 This is a SEM image of the surface of the composite membrane prepared in Example 1 of the present invention;
[0028] Figure 4 This is a SEM image of the cross-section of the composite membrane prepared in Example 1 of the present invention;
[0029] Figure 5 AFM surface image of the composite membrane prepared in Example 1 of this invention;
[0030] Figure 6 This is a surface SEM image of the composite membrane prepared in Example 2 of the present invention before structural stability testing;
[0031] Figure 7 This is a surface SEM image of the composite membrane prepared in Example 2 of the present invention after structural stability testing;
[0032] Figure 8 The images show the X-ray diffraction patterns of the composite membrane prepared in Example 2 of this invention before and after the structural stability test. Detailed Implementation
[0033] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0034] It should be noted that the raw materials used in the embodiments of the present invention are all commercially available; the specific components and their sources are shown in Table 1 below.
[0035] Table 1
[0036]
[0037] Example 1
[0038] This embodiment prepares a composite membrane with α-cyclodextrin-directedly modified MXene, specifically including the following preparation steps:
[0039] (1) Preparation of non-oxidized MXene nanosheet dispersion by reduction-enhanced chemical exfoliation: 1.0 g LiF powder was dissolved in 20 mL of 9 M HCl solution and stirred for about 15 min. Then, 1.0 g Ti3AlC2 was slowly added to the above mixed solution in portions and stirred at 37 °C for 24 h. The resulting reaction solution was centrifuged at 3500 rpm, the supernatant was discarded, and pure water was added for washing. This process was repeated 3 times until the pH of the supernatant was about 6. The centrifuged product was dispersed in 60 mL of pure water and 1.0 g of vitamin C was added. The mixture was sonicated in an ice bath under an argon atmosphere for 0.5 h. The sonicated liquid was centrifuged at 12000 rpm, the supernatant was discarded, and pure water was added for washing. This process was repeated 3 times. After redispersing the centrifuged product, it was centrifuged at 3500 rpm for 1 h to obtain the supernatant, which was the non-oxidized Ti3C2T. x The nanosheet dispersion has a concentration of approximately 3.0 mg / mL.
[0040] (2) Preparation of cyclodextrin inclusion complex through host-guest interaction: 20 mg α-cyclodextrin and 100 mg sodium nicotinate were dissolved in 30 mL of aqueous solution, i.e., the mass ratio of sodium nicotinate to α-cyclodextrin was 5:1. The pH of the solution was adjusted to 8.0 with sodium hydroxide and stirred for 36 h to obtain cyclodextrin inclusion complex solution.
[0041] (3) Preparation of film-forming solution: Add 0.5 mL of Ti3C2T to the cyclodextrin inclusion complex solution in (2). x The nanosheet dispersion was stirred at room temperature for 4 h to obtain the film-forming solution, wherein the concentration of MXene nanosheets was 0.05 mg / L.
[0042] (4) Preparation of α-cyclodextrin-modified MXene composite membrane: Take 5 mL of the membrane preparation solution and vacuum filter it onto a 0.22 μm PVDF filter membrane. After the solution is dried, stop the filtration and slowly add 50 mL of pure water. After soaking for about 10 min, carefully pour off the upper part of the water. Then add another 5 mL of membrane preparation solution and filter again. Repeat this process until the membrane preparation solution is completely removed. Place the filtered membrane in a vacuum drying oven and dry it at 80℃ for 6 h to obtain the α-cyclodextrin-modified MXene composite membrane, wherein the α-cyclodextrin accounts for 7.5% of the mass of the MXene nanosheets.
[0043] Example 2
[0044] This embodiment prepares a composite membrane with α-cyclodextrin-directedly modified MXene, specifically including the following preparation steps:
[0045] (1) Preparation of non-oxidized MXene nanosheet dispersion by reduction-enhanced chemical exfoliation: 2.0 g LiF powder was dissolved in 40 mL of 10 M HCl solution and stirred for about 15 min. Then, 2.0 g Ti3AlC2 was slowly added in portions to the above mixed solution and stirred at room temperature for 24 h. The resulting reaction solution was centrifuged at 3500 rpm, the supernatant was discarded, and pure water was added for washing. This process was repeated 3 times until the pH of the supernatant was about 6. The centrifuged product was dispersed in 120 mL of pure water and 2.0 g of vitamin C was added. The mixture was sonicated in an ice bath under an argon atmosphere for 0.5 h. The sonicated liquid was centrifuged at 12000 rpm, the supernatant was discarded, and pure water was added for washing. This process was repeated 3 times. After redispersing the centrifuged product, it was centrifuged at 3500 rpm for 1 h to obtain the supernatant, which was the non-oxidized Ti3C2T. x The nanosheet dispersion has a concentration of approximately 3.0 mg / mL.
[0046] (2) Preparation of cyclodextrin inclusion complex through host-guest interaction: 10 mg α-cyclodextrin and 80 mg potassium nicotinate were dissolved in 30 mL of aqueous solution, i.e., the mass ratio of potassium nicotinate to α-cyclodextrin was 8:1. The pH of the solution was adjusted to 7.0 and stirred for 24 h to obtain the cyclodextrin inclusion complex solution.
[0047] (3) Preparation of film-forming solution: Add 0.5 mL of Ti3C2T to the cyclodextrin inclusion complex solution in (2). x The nanosheet dispersion was stirred at room temperature for 6 h to obtain the film-forming solution.
[0048] (4) Preparation of α-cyclodextrin-modified MXene composite membrane: Take 4 mL of the membrane preparation solution and vacuum filter it onto a 0.22 μm PES filter membrane. After the solution is dried, stop the filtration and slowly add 20 mL of pure water. After soaking for about 10 min, carefully pour off the upper part of the water. Then add another 4 mL of the membrane preparation solution and filter again. Repeat this process until the membrane preparation solution is completely removed. Place the filtered membrane in a vacuum drying oven and dry it at 60℃ for 2 h to obtain the α-cyclodextrin-modified MXene composite membrane, wherein the α-cyclodextrin accounts for 15% of the mass of the MXene nanosheets.
[0049] Example 3
[0050] The preparation method of this embodiment is basically the same as that of Example 1. The difference is that in step (2), the amount of α-cyclodextrin added is 20 mg; the mass ratio of sodium nicotinate to α-cyclodextrin is 10:1, and finally a composite film of MXene modified by α-cyclodextrin is obtained, wherein the α-cyclodextrin is 7.5% of the mass of MXene nanosheets.
[0051] Example 4
[0052] The preparation method of this embodiment is basically the same as that of Example 1, except that in step (3), non-oxidized Ti3C2T is added to the cyclodextrin inclusion complex solution. x The amount of nanosheet dispersion was 2.0 mL, and a composite film of MXene modified with α-cyclodextrin was finally obtained, wherein the α-cyclodextrin was 3% of the mass of MXene nanosheets.
[0053] Example 5
[0054] The preparation method of this embodiment is basically the same as that of Example 1. The difference is that in step (2), the amount of α-cyclodextrin added is 12.5 mg; the mass ratio of sodium nicotinate to α-cyclodextrin is 10:1, and finally a composite film of MXene modified by α-cyclodextrin is obtained, wherein α-cyclodextrin is 12% of the mass of MXene nanosheets.
[0055] Comparative Example 1
[0056] The difference between this comparative example and Example 1 is that only MXene is used as the ion separation membrane. The specific preparation method is as follows:
[0057] (1) Dissolve 1.0 g LiF powder in 20 mL of 9 M HCl solution and stir for about 15 min. Then, slowly add 1.0 g Ti3AlC2 in portions to the above mixed solution and stir at 37 °C for 24 h. Centrifuge the resulting reaction solution at 3500 rpm, discard the supernatant, wash with pure water, and repeat 3 times until the pH of the supernatant is about 6. Disperse the centrifuged product in 60 mL of pure water and add 1.0 g of vitamin C. Sonicate in an ice bath under an argon atmosphere for 0.5 h. Centrifuge the sonicated liquid at 12000 rpm, discard the supernatant, wash with pure water, and repeat 3 times. After redispersing the centrifuged product, centrifuge at 3500 rpm for 1 h to obtain the supernatant, which is the non-oxidized Ti3C2T. x The nanosheet dispersion has a concentration of approximately 3.0 mg / mL.
[0058] (2) Take 5 mL of the membrane-forming solution and vacuum filter it onto a 0.22 μm PVDF filter membrane. After the solution is dried, stop the filtration and slowly add 50 mL of pure water. Soak for about 10 min, then carefully pour off the water. Then add another 5 mL of the membrane-forming solution and filter again. Repeat this process until all the membrane-forming solution is removed. Place the filtered membrane in a vacuum drying oven and dry it at 80℃ for 6 h to obtain a pure MXene ion separation membrane.
[0059] Comparative Example 2
[0060] The difference between this comparative example and Example 1 is that no cyclodextrin inclusion complex is formed; instead, MXene nanosheets are directly combined with α-cyclodextrin. The preparation method is as follows:
[0061] (1) Preparation of non-oxidized MXene nanosheet dispersion by reduction-enhanced chemical exfoliation: 1.0 g LiF powder was dissolved in 20 mL of 9 M HCl solution and stirred for about 15 min. Then, 1.0 g Ti3AlC2 was slowly added to the above mixed solution in portions and stirred at 37 °C for 24 h. The resulting reaction solution was centrifuged at 3500 rpm, the supernatant was discarded, and pure water was added for washing. This process was repeated 3 times until the pH of the supernatant was about 6. The centrifuged product was dispersed in 60 mL of pure water and 1.0 g of vitamin C was added. The mixture was sonicated in an ice bath under an argon atmosphere for 0.5 h. The sonicated liquid was centrifuged at 12000 rpm, the supernatant was discarded, and pure water was added for washing. This process was repeated 3 times. After redispersing the centrifuged product, it was centrifuged at 3500 rpm for 1 h to obtain the supernatant, which was the non-oxidized Ti3C2T. x The nanosheet solution dispersion has a concentration of approximately 3.0 mg / mL.
[0062] (2) Preparation of film-forming solution: Dissolve 20 mg of α-cyclodextrin in 30 ml of aqueous solution, and then add 0.5 ml of Ti3C2T x The nanosheet solution was stirred at room temperature for 4 hours to obtain the film-forming solution.
[0063] (3) Preparation of α-cyclodextrin-modified MXene composite membrane: Take 5 mL of the membrane preparation solution and vacuum filter it onto a 0.22 μm PVDF filter membrane. After the solution is dried, stop the filtration and slowly add 50 mL of pure water. After soaking for about 10 min, carefully pour off the upper part of the water. Then add another 5 mL of the membrane preparation solution and filter again. Repeat this process until the membrane preparation solution is completely removed. Place the filtered membrane in a vacuum drying oven and dry it at 80℃ for 6 h to obtain the α-cyclodextrin-modified ion separation membrane.
[0064] Comparative Example 3
[0065] The preparation method of this comparative example is basically the same as that of Example 1. The difference is that in step (2), the mass of α-cyclodextrin is 100 mg and the mass of sodium nicotinate is 500 mg, and a cyclodextrin inclusion complex with a mass ratio of sodium nicotinate to α-cyclodextrin of 5:1 is obtained. In the obtained α-cyclodextrin-modified MXene composite film, the α-cyclodextrin is 1.5% of the mass of MXene nanosheets.
[0066] Comparative Example 4
[0067] The preparation method of this comparative example is basically the same as that of Example 1. The difference is that in step (2), the mass of α-cyclodextrin is 3 mg and the mass of sodium nicotinate is 30 mg, and a cyclodextrin inclusion complex with a mass ratio of sodium nicotinate to α-cyclodextrin of 10:1 is obtained. In the obtained α-cyclodextrin-modified MXene composite film, α-cyclodextrin accounts for 50% of the mass of MXene nanosheets.
[0068] Comparative Example 5
[0069] The preparation method of this comparative example is basically the same as that of Example 1. The difference is that in step (4), the batch filtration and washing are not performed during the filtration. The specific method of step (4) is as follows: Take the membrane preparation solution and vacuum filter it onto a 0.22 μm PVDF filter membrane. After the solution is dried, slowly add 50 mL of pure water, soak for about 10 min, carefully pour out the upper part of the water, and filter again. Place the filtered membrane into a vacuum drying chamber and dry it at 80℃ for 6 h to obtain the α-cyclodextrin-directed modified MXene composite membrane.
[0070] Performance testing
[0071] I. Ion Separation Performance Test
[0072] Ion separation tests were conducted on the ion separation membranes provided in Examples 1-5 and Comparative Examples 1-2. The test conditions were a mixed salt system (LiCl, NaCl, KCl, MgCl2, CaCl2, all with a concentration of 0.2 M), a stabilization time of 1 h plus a test time of 1 h, and the permeation ion concentration was tested using ICP-OES. The ion selectivity and monovalent ion flux were calculated, and the results are shown in Table 2.
[0073] Table 2
[0074]
[0075] II. Stability Testing of Composite Membrane Structures
[0076] The composite membrane prepared in Example 1 was subjected to ion separation testing under actual saline lake water conditions for 7 days. SEM and XRD characterization of the composite membrane were performed before and after the test. The SEM results showed that... Figures 6-7 As shown, the microstructure of the composite film did not change significantly before and after the test, and no defects appeared; XRD characterization results showed that, as Figure 8 As shown, the interlayer structure of the composite membrane remained consistent before and after the test. In summary, this composite membrane possesses a certain degree of long-term stability.
[0077] The composite membranes prepared in Examples 1-5 have the following structures: Figures 1-2 As shown, α-cyclodextrin molecules first increase the negative charge density at the narrow end by forming inclusion complexes, while the edges of MXene nanosheets are positively charged, thus inducing the directional distribution of α-cyclodextrin inclusion complexes at the edges of the nanosheets. Subsequently, α-cyclodextrin molecules form stable metal-O covalent bonds with the nanosheet edges. When MXene nanosheets are stacked layer by layer to form sub-nanochannels, the α-cyclodextrin molecules connected to the ends of the nanosheets form channel entrances in pairs. Furthermore, since the α-cyclodextrin in the composite film is located at the ends of the MXene nanosheets, the channel entrances formed by the α-cyclodextrin are located at the edges of the sub-nanochannels, as shown in the diagram. Figure 2 As shown, they can also be located between sub-nanometer channels, such as... Figure 1 As shown.
[0078] The composite membrane prepared in Example 1 was structurally characterized, such as... Figure 3 The image shown is a SEM image of the composite membrane surface; as shown... Figure 4 As shown, this is a SEM image of the composite membrane cross-section; and as shown... Figure 5 The image shown is the AFM pattern of the composite membrane surface; Figures 3-5It is evident that α-cyclodextrin in the composite membrane exists only at the entrance of the interlayer channel, while the channel interior remains unmodified, maintaining a unique structure. This allows ion recognition and separation to occur only at the channel entrance, while ion transport takes place within the unmodified channel, thus improving ion selectivity and ensuring ion flux.
[0079] As shown in Table 2, the composite films prepared in Examples 1-5 show that Li + Flux not less than 0.088 mol / m -2 h -1 K + Flux not less than 0.397 mol / m -2 h -1 It is evident that in the composite membrane, monovalent metal ions, after passing through α-cyclodextrin, enter the unmodified channels, enabling unimpeded transport and thus achieving high-throughput delivery; while Li + / Mg 2+ The minimum selectivity is 457, K + / Mg 2+ The selectivity lowest position is 2040, indicating that α-cyclodextrin binds to MXene at the channel port via covalent interactions, achieving ion separation through different binding interactions with metal ions; monovalent ions such as K + The high binding energy with cyclodextrins provides energy compensation for ion dehydration, promoting their entry into the cyclodextrin cavity and thus rapid transport. Divalent ions such as Mg... 2+ Because of the relatively low binding energy between the stable hydrated layer and cyclodextrin, it is difficult for cyclodextrin molecules to enter the cyclodextrin cavity due to steric exclusion, thus hindering the separation of monovalent and divalent metal ions. α-Cyclodextrin exists only at the entrance of the interlayer channel and is directionally distributed through metal-O bonds, exhibiting tight binding. The cyclodextrin molecules at the channel entrance selectively separate metal ions, while the unmodified interlayer channel, maintaining its original state, facilitates rapid ion transport, simultaneously improving ion selectivity and flux.
[0080] The data from Example 1 and Comparative Example 1 show that the pure MXene membrane does not have high ion selectivity and ion flux.
[0081] The data from Example 1 and Comparative Example 2 show that if nicotinic acid salt is not added in advance to form a cyclodextrin inclusion complex, the directional binding behavior of α-cyclodextrin molecules and MXene nanosheets will be weakened. α-cyclodextrin molecules not only exist at the channel entrance but also enter the channel interior, which will lead to the expansion and blockage of the interlayer channels. At the same time, it will cause ions to bypass the recognition function of cyclodextrin, thus making it impossible to achieve ion selective separation and high-throughput transport.
[0082] The data from Example 1 and Comparative Examples 3 and 4 show that the content of cyclodextrin inclusion complex has a significant impact on the ion separation performance of the composite membrane; too much or too little content cannot simultaneously achieve high ion selectivity and high ion flux.
[0083] The data from Example 1 and Comparative Example 5 show that if a batch washing step is not performed during the filtration membrane formation process, nicotinic acid salts will not be detached, resulting in α-cyclodextrin remaining as an inclusion complex. On the one hand, cyclodextrin existing as an inclusion complex will cause blockage of the two-dimensional channel, greatly reducing ion permeability and thus failing to achieve high ion flux. On the other hand, cyclodextrin inclusion complexes cannot accurately identify monovalent and divalent ions, thus reducing their ion selective separation.
[0084] The composite membrane provided by this invention, which is orientedly modified with α-cyclodextrin to create MXene nanosheets, exhibits a partitioned structure of selective and permeable regions, which significantly enhances ion selectivity while increasing ion flux. When applied to the separation of mixed salt solutions, the monovalent ion flux reaches 0.5 mol / m³. -2 h -1 The selectivity for monovalent and divalent ions exceeds 10. 3 Meanwhile, the strong covalent phase interaction between α-cyclodextrin and MXene nanosheets can tightly pull adjacent nanosheets together, enhancing the mechanical properties of the membrane and extending its service life.
[0085] In addition to the above embodiments, it should be noted that the mass of α-cyclodextrin in the composite membrane provided by the present invention can be 3-15% of the mass of MXene nanosheets; the mass ratio of nicotinate to α-cyclodextrin in the composite membrane prepared by the method of the present invention can be (5-10):1; the concentration of MXene nanosheets in the film-forming solution can be 0.05-0.2 g / L; that is, the technical effects claimed by the present invention can be achieved by using the preparation process and the defined parameter range of the present invention, and therefore no further examples will be given to support this claim.
Claims
1. A composite membrane with α-cyclodextrin directionally modified MXene, characterized in that, include: MXene nanosheets, which are stacked layer by layer to form sub-nanometer channels that facilitate the passage of ions; α-Cyclodextrin, which is attached to the ends of MXene nanosheets to form interlayer channel entrances for sub-nanochannels.
2. The MXene membrane oriented with α-cyclodextrin according to claim 1, characterized in that, The MXene nanosheets are Ti3C2T x Ti2CT x V2CT x or Nb2CT x One of them.
3. The MXene membrane orientedly modified with α-cyclodextrin according to claim 1, characterized in that, The mass of the MXene nanosheets is 3-15% of the mass of α-cyclodextrin.
4. A method for preparing an MXene membrane directionally modified with α-cyclodextrin according to any one of claims 1-3, characterized in that, Includes the following steps: (1) An aqueous dispersion of non-oxidized MXene nanosheets was prepared by a reduction-enhanced chemical exfoliation method; (2) Dissolve α-cyclodextrin and nicotinic acid salt in water to form a mixed aqueous solution, and stir to form a cyclodextrin inclusion complex solution; (3) Add the aqueous dispersion of MXene nanosheets to the aqueous solution of cyclodextrin inclusion complex and stir to obtain the film-forming solution; (4) The membrane-forming solution is deposited onto the base membrane by batch filtration. Each batch is washed to remove nicotinic acid molecules after deposition. After filtration, the membrane is dried to obtain the composite membrane.
5. The method for preparing an MXene membrane directionally modified with α-cyclodextrin according to claim 4, characterized in that, The reduction-enhanced chemical exfoliation method for preparing an aqueous dispersion of MXene nanosheets includes the following steps: lithium fluoride and MAX powder are added uniformly to a concentrated hydrochloric acid solution and stirred until homogeneous; then, after etching at 25-45°C for 24 h, multilayer MXene nanosheets are obtained by centrifugation; then, a reducing agent is added to the aqueous MXene nanosheet solution, followed by ultrasonic exfoliation under an inert atmosphere, and then centrifugation and washing to obtain a single-layer non-oxidized MXene nanosheet dispersion.
6. The method for preparing an MXene membrane directionally modified with α-cyclodextrin according to claim 5, characterized in that, The mass ratio of the reducing agent to MAX powder is (0.5-2):
1.
7. The method for preparing an MXene membrane directionally modified with α-cyclodextrin according to claim 4, characterized in that, The nicotinate is one of sodium nicotinate, potassium nicotinate, or lithium nicotinate.
8. The method for preparing an MXene membrane directionally modified with α-cyclodextrin according to claim 4, characterized in that, The mass ratio of nicotinic acid salt to α-cyclodextrin is (5-10):1; the pH of the mixed aqueous solution is 6-9; and the stirring time is 24-48 h.
9. The method for preparing an MXene membrane directionally modified with α-cyclodextrin according to claim 4, characterized in that, The concentration of MXene nanosheets in the film-forming solution is 0.05-0.2 g / L, and the stirring reaction time is 2-6 h.
10. The method for preparing an MXene membrane directionally modified with α-cyclodextrin according to claim 4, characterized in that, The base film is any one of PES, PVDF or Nylon, and the pore size of the base film is 0.1-0.22 μm.
Citation Information
Patent Citations
Method for preparing peptide emulsion formulation
US20230055555A1
Cyclodextrin derivatives having at least one nitrogen-containing heterocycle, their preparation and use
US5728823A
Cited By
Dehydration resistance reduction type ion exchange membrane as well as preparation method and application thereof
CN121846913A
A dehydration and drag-reducing ion exchange membrane, its preparation method and application
CN121846913B